Experimentally reduced insulin/IGF‐1 signaling in adulthood extends lifespan of parents and improves Darwinian fitness of their offspring. Issue 2 (4th March 2019) - Lind, Martin I.; Ravindran, Sanjana; Sekajova, Zuzana; Carlsson, Hanne; Hinas, Andrea; Maklakov, Alexei A.
Abstract: Classical theory maintains that ageing evolves via energy trade‐offs between reproduction and survival leading to accumulation of unrepaired cellular damage with age. In contrast, the emerging new theory postulates that ageing evolves because of deleterious late‐life hyper‐function of reproduction‐promoting genes leading to excessive biosynthesis in late‐life. The hyper‐function theory uniquely predicts that optimizing nutrient‐sensing molecular signaling in adulthood can simultaneously postpone ageing and increase Darwinian fitness. Here, we show that reducing evolutionarily conserved insulin/IGF‐1 nutrient‐sensing signaling via daf‐2 RNA interference (RNAi) fulfils this prediction in Caenorhabditis elegans nematodes. Long‐lived daf‐2 RNAi parents showed normal fecundity as self‐fertilizing hermaphrodites and improved late‐life reproduction when mated to males. Remarkably, the offspring of daf‐2 RNAi parents had higher Darwinian fitness across three different genotypes. Thus, reduced nutrient‐sensing signaling in adulthood improves both parental longevity and offspring fitness supporting the emerging view that suboptimal gene expression in late‐life lies at the heart of ageing.